2016
DOI: 10.1002/pro.2873
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of amino acid substitutions in AraC variants that respond to triacetic acid lactone

Abstract: The Escherichia coli regulatory protein AraC regulates expression of ara genes in response to L-arabinose. In efforts to develop genetically encoded molecular reporters, we previously engineered an AraC variant that responds to the compound triacetic acid lactone (TAL). This variant (named "AraC-TAL1") was isolated by screening a library of AraC variants, in which five amino acid positions in the ligand-binding pocket were simultaneously randomized. Screening was carried out through multiple rounds of alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our previous studies show that our AraC-based TAL sensors also respond to one or more compounds that are structurally similar to TAL, such as 4-hydroxy-3,6-dimethyl TAL (4H36M TAL), and 2-hydroxybenzoic acid (salicylic acid) (Frei et al 2016, Frei, Qian and. We find similar ligand promiscuity for these new TAL sensors, with results summarized in Table 2 (response curves are given in Figure S2 and Figure S3).…”
Section: A Tal Sensor With Improved Specificitysupporting
confidence: 65%
See 1 more Smart Citation
“…Our previous studies show that our AraC-based TAL sensors also respond to one or more compounds that are structurally similar to TAL, such as 4-hydroxy-3,6-dimethyl TAL (4H36M TAL), and 2-hydroxybenzoic acid (salicylic acid) (Frei et al 2016, Frei, Qian and. We find similar ligand promiscuity for these new TAL sensors, with results summarized in Table 2 (response curves are given in Figure S2 and Figure S3).…”
Section: A Tal Sensor With Improved Specificitysupporting
confidence: 65%
“…Plasmid pPCC1322 (map and sequence in Supplementary Materials) was constructed from pFG29-TAL (Frei et al 2016) as follows: the f1 origin, together with ~1 kb non-coding sequence flanking the f1 origin, was removed from pFG29-TAL, and the ribosome binding site (RBS) region of AraC-TAL1 was modified to achieve a lower translation initiation rate for AraC-TAL1 or its variants. Library enrichment with tetA-dual selection was carried out with plasmids pPCC1340 and pPCC1342.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…While a wide variety of natural TFs that respond to a broad spectrum of small molecules have been characterized, it is still often desired or necessary to tune TF inducer sensitivity and/or specificity for specific applications. Through saturation mutagenesis and FACS screening, the Larabinose-responsive TF AraC from E. coli has been engineered to respond to D-arabinose [31], mevalonate [7], triacetic acid lactone (TAL) [8] [32], and ectoine [9]. The AraC-based mevalonate sensor was linked to LacZ reporter expression (blue/white colony screening) to identify enhanced mevalonate-producing E. coli clones from a library of randomized RBS-region sequences upstream of tHMGR, encoding HMG-CoA reductase [7].…”
Section: Target Compound Directly Induces Gene Expressionmentioning
confidence: 99%
“…For this reason, we aimed to construct an alternative xylulose sensor, by exploiting components of the L-arabinose operon, native to E. coli [15]. Several previous studies have shown that its regulatory protein, AraC, can be engineered to activate transcription in response to non-native small molecules [16][17] [18]. Sitesaturation mutagenesis of residues positioned within the ligand-binding pocket of AraC (Fig 1), coupled with fluorescence-based cell sorting, allowed isolation of AraC variants with altered effector specificity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Split regulatory components of the L-arabinose operon from E. coli are functional and can be used for construction of L-arabinose-inducible systems As the P. fluorescens MtlR regulatory system lacked specificity in E. coli, we aimed to utilize components of the L-arabinose operon from E. coli to generate a new tightlycontrolled xylulose-regulatory system. We chose to mutagenize the AraC protein to change its effector specificity, based on previous reports of successful engineering of AraC to respond to non-native inducers[16][17][18]. The p BAD promoter is regulated by the AraC transcriptional regulator, which drives expression from p BAD only in presence of L-arabinose[15].…”
mentioning
confidence: 99%